2013
DOI: 10.1016/j.vaccine.2013.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic humoral immunity to Bacillus anthracis protective antigen: Identification of anti-peptide IgG correlating with seroconversion to Lethal Toxin neutralization

Abstract: A substantial fraction of individuals vaccinated against anthrax have low to immeasurable levels of serum Lethal Toxin (LeTx)-neutralizing activity. The only known correlate of protection against Bacillus anthracis in the currently licensed vaccine is magnitude of the IgG response to Protective Antigen (PA); however, some individuals producing high serum levels of anti-PA IgG fail to neutralize LeTx in vitro. This suggests that non-protective humoral responses to PA may be immunodominant in some individuals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Strikingly, in contrast to the endogenous Tcra -intact double Tg model, all Tcra −/− 3B5.8/hLa double Tg mice developed high-titer serum IgG antibodies to recombinant hLa antigen but not to an irrelevant foreign antigen from Bacillus anthracis (6xhis-PA) that is immunogenic in H-2 k mice (32) (Fig. 6B).…”
Section: Resultsmentioning
confidence: 98%
“…Strikingly, in contrast to the endogenous Tcra -intact double Tg model, all Tcra −/− 3B5.8/hLa double Tg mice developed high-titer serum IgG antibodies to recombinant hLa antigen but not to an irrelevant foreign antigen from Bacillus anthracis (6xhis-PA) that is immunogenic in H-2 k mice (32) (Fig. 6B).…”
Section: Resultsmentioning
confidence: 98%
“…Our laboratory has previously reported sequential B cell epitopes of LF [13], EF [30] and PA [31] in A/J mice, but this is our first report of PA epitopes in B6 or B6.H2k mice. The previous reports demonstrated that identification of sequential B cell epitopes in mice is highly reproducible, in terms of both epitopes identified and relative magnitude of responses to individual epitopes, if pools of serum from groups of immunized mice are evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The source of variation in these responses in unclear. We previously demonstrated in genetically identical mice that substantial epitope variation in the response to immunization with PA is stochastic (59).…”
Section: Discussionmentioning
confidence: 99%